Tick‐borne encephalitis virus and West‐Nile fever virus as causes of serous meningitis of unknown origin in Kazakhstan. (23rd March 2022) - Shin, Anna; Tukhanova, Nur; Ndenkeh, Jackson; Shapiyeva, Zhanna; Yegemberdiyeva, Ravilya; Yeraliyeva, Lyazzat; Nurmakhanov, Talgat; Froeschl, Guenter; Hoelscher, Michael; Musralina, Lyazzat; Toktasyn, Yerubayev; Gulnara, Zhumabaeva; et al.
Abstract: Flaviviruses are a family of viruses that cause many diseases in humans. Their similarity in the antigenic structure causes a cross‐reaction, which complicates the precise diagnostic of disease causing agents. Tick‐borne encephalitis virus (TBEV), a member of the flavivirus family, is the cause of tick‐borne encephalitis (TBE). Worldwide the awareness of this disease is raising, however, in many countries such as the Republic of Kazakhstan (KZ) there is a lack of serological investigation of flaviviruses in humans. In our study, we focused on two TBE endemic regions of KZ (East Kazakhstan Oblast (EKO) and Almaty (AO)) and a region where TBE cases were registered only since 2010 (Akmola Oblast (AkO)). In KZ, up to 400 cases of serous meningitis of unknown origin were registered annually in the period from 2017 to 2019. Our goals were to calculate the prevalence of antibodies against TBEV in patients with suspected meningitis. We collected 179 sera and 130 cerebrospinal fluid (CSF) samples from patients and included a questionnaire with focus on socio‐demographical factors and observed tick bites. The human samples were tested with TBEV and West‐Nile fever virus (WNFV) IgM and IgG ELISA, by immunofluorescence assay using a flavivirus biochip, and TBEV‐specific real‐time RT‐PCR. We found TBEV and WNFV antibodies in 31 samples by serological and molecular techniques. Seven serum samples out of 31 showed TBEV‐specific antibodies, and three serum pairs had WNFV antibodies. Correlating the serological results with the information gained from the questionnaires it becomes apparent that the number of tick bites is a significant factor for a TBEV infection. This result has an impact on diagnostic in KZ and physicians should be aware that both flaviviruses play a role for serous meningitis of unknown origin in KZ.